The role of need for self-expression and arousal to commit university students for environmental responsibility behaviours - Loureiro, S. M. C.; Koo, D.-M.; Breazeale, M. (World Review of Entrepreneurship, Management and Sustainable Development, 2018)
University social responsibility as recycling and environmental protection attitude is a core issue in higher education. However, scarce research examines the factors that influence individuals’ commitment to recycling and environmental preservation, and even less explores how that commitment can lead to preferential behavior, word of mouth and willingness to sacrifice for recycling and environmental preservation. This study examines the roles of need for self-expression and arousal to explain commitment and whether commitment leads to those behaviors. The study is duplicated in three countries, each representing different cultural dimensions. Data collected from participants at Universities in South Korea, the United States and Portugal inform a model that supports the majority of the hypotheses and points out some interesting differences in the ways that recycling and environmental preservation should be presented in various cultures to achieve buy-in and behavior change.